Nutritional and non-nutritional factors affecting learning achievement of primary school pupils implications for educational policy and administration - Dominguez, Salome Peredo
A total of 1,440 pupil respondents from 40 randomly chosen schools in three Luzon regions were given standardized achievement and mental ability tests developed by the Ministry of Education, Culture and Sports and standard measurement of height-for-age for Filipinos. Their parents, teachers and school heads were interviewed to get additional information about the child, the school and the home environment. Multiple regression analysis showed that the nutritional status as indicated by height-for-age was a significant predictor for Grade I in Mathematics and Grade 2 in Language, Math and Pagbasa but not for the higher grade levels. The school, home, and child factors found to influence pupil achievement are teacher's ability, pupil-teacher ratio, father's education, presence of educational materials in the home, and the child's initial mental ability and sex.